ARCE SÁNCHEZ, M.; CONEJO GARROTE, L.; MUÑOZ ESCOLANO, J.M. (2019). Aprendizaje y enseñanza de las matemáticas. Madrid: Síntesis, 350 páginas, ISBN 978-84-9171-265-7 - Antonio M. Oller-Marcén (Universidad de La Rioja, 2020)
ARCE SÁNCHEZ, M.; CONEJO GARROTE, L.; MUÑOZ ESCOLANO, J.M. (2019). Aprendizaje y enseñanza de las matemáticas. Madrid: Síntesis, 350 páginas, ISBN 978-84-9171-265-7.